Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1016/j.bbamem.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

T cell antigen receptor activation and actin cytoskeleton remodeling

Abstract: T cells constitute a crucial arm of the adaptive immune system and their optimal function is required for a healthy immune response. After the initial step of T cell-receptor (TCR) triggering by antigenic peptide complexes on antigen presenting cell (APC), the T cell exhibits extensive cytoskeletal remodeling. This cytoskeletal remodeling leads to formation of an “immunological synapse” [1] characterized by regulated clustering, segregation and movement of receptors at the interface. Synapse formation regulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
149
0
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(165 citation statements)
references
References 134 publications
2
149
0
9
Order By: Relevance
“…Microvilli are enriched with bundled actin and their stability depends on actin polymerization (1). We therefore treated T cells with the actin-disrupting toxin latrunculin-A (Lat-A), which stabilizes G-actin monomers and prevents actin polymerization (44). SEM images confirmed that most of the microvilli of these lymphocytes disappeared within a 30-min exposure to the Lat-A toxin, both in the case of resting T cells (Fig.…”
Section: Distribution Of Tcrs In Relation To the 3d Topography Of Thementioning
confidence: 80%
“…Microvilli are enriched with bundled actin and their stability depends on actin polymerization (1). We therefore treated T cells with the actin-disrupting toxin latrunculin-A (Lat-A), which stabilizes G-actin monomers and prevents actin polymerization (44). SEM images confirmed that most of the microvilli of these lymphocytes disappeared within a 30-min exposure to the Lat-A toxin, both in the case of resting T cells (Fig.…”
Section: Distribution Of Tcrs In Relation To the 3d Topography Of Thementioning
confidence: 80%
“…Engagement of the T cell antigen receptor (TCR) by cognate peptide major histocompatibility complex ( pMHC) triggers the assembly of the immunological synapse (IS), a dynamic supra-molecular membrane structure formed at the contact between the T cell and antigen-presenting cell (APC) (Kumari et al, 2014;Fooksman et al, 2010). In addition to organizing signal propagation, the IS likely participates in signal processing required for adequate T cell activation (Acuto et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the spectrin and ankyrin cyoskeletal systems, actin polymerization has also been shown to play a prominent role in cholesterol dependent signal domain aggregation and synapse formation during T cell activation. 44,[59][60][61][62][63] In turn, we looked at whether blockade of actin polymerization influenced the activating effects of mild heating and ethanol, and found that in both cases actin polymerization was necessary for enhancement of IL-2 production (Fig. 5C).…”
Section: Discussionmentioning
confidence: 99%